Patients' views on their experience of the delivery of single-sex accommodation within the endoscopy department: is it worth it?. Issue 1 (14th March 2016) - Wiseman, Elizabeth F; Chatten, Kelly; Shah, Sita; Keld, Richard R; Ang, Yeng S
Abstract : Introduction: Provision of single-sex accommodation (SSA) in hospitals is a key National Health Service objective. Department of Health policy to eliminate mixed-sex accommodation (MSA) was implemented in our endoscopy department in 2011. We found no published studies of patients' views on MSA in endoscopy units. Aim: We explored patients' views on MSA and their experience of attending our unit at Royal Albert Edward Infirmary (Wigan, UK) since implementation of the SSA policy. Methods: Patients attending the endoscopy unit August–October 2012 and February–April 2015 were invited to participate. Views were surveyed using a 10-point questionnaire. Results: 155 patients were included. A minority were aware of national (36%) or local (39%) policies regarding MSA provision. Only 20.0% and 22.9% reported that they would feel uncomfortable changing behind a curtain or waiting in a gown in a mixed-sex area, respectively. Most of those that felt uncomfortable (81% and 71%) were female, and women ranked importance of SSA significantly higher than men. However, both sexes ranked importance of SSA significantly lower than that of prompt investigation/treatment. Admissions to an alternative recovery area specifically to maintain SSA compliance reduced from 25% (2012) to 8% (2015), following simple measures to improve list efficiency, with corollary reduction in reports of compromised patient experience. Conclusions: SSA is an important healthcare priority for some patients, especially women. However, most consider prompt investigation/treatment a much higher priority. Measures to comply with SSA can negatively affect patient experience. However, we demonstrate that simple measures can result in significant improvements in service delivery and patient experience while remaining compliant with SSA guidance.